Understanding the purchasing behavior of Agri-food commodities in Malaysia using the Apriori algorithm - Tanakinjal, Geoffrey Harvey; Boniface, Bonaventure; Kamu, Assis; Kogid, Mori; Sondoh, Stephen L.; Gugkang, Alesia Sigang; Krishnan, Anath Rau; Alfred, Rayner; Arumugam, Nalini; Mohd Nawi, Nolila; Liew, Venus Khim Sen; Entebang, Harry (Springer Nature, 2024)
Uncovering the relationships between agri-food commodities in Malaysia is instrumental for making informed decisions at various levels, from individual farmers to policymakers. It supports economic growth, sustainable practices, and the overall well-being of the population. Market basket analysis can be used to provide valuable insights into the relationships between different items in a dataset and can be used for decision-making, recommendation systems, and optimizing business processes. The aim of this paper is to investigate the relationships between agri-food commodities in Malaysia as it provides insights into consumer preferences and behavior. The paper presents the findings obtained related to the application of Apriori algorithm to investigate the relationship between agri-food commodities bought in Malaysia for the whole year 2022. Datasets were collected from February 2022 through January 2023 which consists of 56878 number of transactions recorded with 324 number of unique items. This also will expose the purchase pattern behavior for all the households in Malaysia. Based on the findings of this paper, the extracted rule which has the highest LIFT’ value states that when chicken (Keratan Daging Ayam), other vegetables (Lain-lain Sayur-sayuran) and fish (Ikan) occur together, it is likely or observed that fruit (Lain-lain Buah-buahan) is also present. This rule has the highest LIFT’s value of 26.4 for the vegetable commodity. This paper also presented and described the relationships between five selected popular commodities with other commodities. The extracted rules can be applied to any small to large-scale agri-food shopping market or mall. For future works, a more comprehensive validation works is required to validate these extracted rules so that they can be applied by any private or public agencies in Malaysia.